A protocol for ongoing systematic scoping reviews of World Trade Center Health research. - Concannon, Thomas W; Chari, Ramya.; Lee, Justin.; Hiatt, Liisa.; Faherty, Laura J (Tufts University. Tisch Library., 2023)
Keywords: World Trade Center, Disaster, 9/11 attacks, Translational research, Health.; Springer Open.